2006
DOI: 10.1016/j.jcf.2005.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of cystic fibrosis associated with R117H on a background of 7T polythymidine tract at intron 8

Abstract: We report late diagnoses of cystic fibrosis (CF) in two men aged 61 and 65 years. At the time of presentation, both patients had significant pulmonary disease. In each case two CFTR gene mutations were identified, including R117H on a background of a poly T genotype of 7T/9T. Patients with two identified CFTR mutations which include the R117H/7T anomaly should be followed up routinely as they remain susceptible to severe lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 13 publications
1
31
0
2
Order By: Relevance
“…Ninety-four percent of the p.R117H-positive individuals with a second mutation did not carry a 5T allele. p.R117H in cis with 5T generally confers moderate to severe CF, whereas p.R117H in cis with 7T may confer a mild form of CF, a later CF onset, CBAVD, or no apparent disease (35)(36)(37). Similarly, other mutations identified in carriers of 2 mutations have been associated with variable phenotypic expression ranging from classic disease to CBAVD in adults or an asymptomatic phenotype when identified in the neonatal period (24 -28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-four percent of the p.R117H-positive individuals with a second mutation did not carry a 5T allele. p.R117H in cis with 5T generally confers moderate to severe CF, whereas p.R117H in cis with 7T may confer a mild form of CF, a later CF onset, CBAVD, or no apparent disease (35)(36)(37). Similarly, other mutations identified in carriers of 2 mutations have been associated with variable phenotypic expression ranging from classic disease to CBAVD in adults or an asymptomatic phenotype when identified in the neonatal period (24 -28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some haplotypes contain loci mutually influencing the gene function, such as the R117H-poly-T association; [12][13][14] others are neutral or ameliorative. A detailed in phase description of the current study haplotypes is shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…It affects exocrine glands, impacting upon sweat production and regulation, the gastro-intestinal tract, most notably the pancreas, and reproductive systems; lung disease continues to be the major cause of morbidity and mortality (Ren et al 2011). CF is caused by mutations of a gene in chromosome 7 that encodes amino acid protein 1480, the cystic fibrosis transmembrane conductance regulator (CFTR) protein (Peckham et al 2006). Amino acids block the formation of CFTR protein, thus if any are missing or irregular the CFTR protein may cease to function correctly (Mayall et al 2009).…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Common respiratory symptoms in adolescents with CF include: a persistent cough, sinusitis, mucous amassing, resulting in inflammation, bacteria accumulation and subsequent pneumonia (Twyman et al 2010;Peckham et al 2006) and these are frequent concerns for Ellen. Hence, she is prescribed Colistimethate Sodium via a nebuliser twice daily, Tobramycin podhaler twice daily, Salbutamol evohaler as required and hypertonic sodium chloride solution for physiotherapy, required twice daily.…”
Section: Planning Ellen's Nursing Carementioning
confidence: 99%